Have Dutch Municipalities Become More Efficient in Managing the Costs of Social Assistance Dependency? - Lourens Broersma; Arjen Edzes; Jouke Van Dijk (European Regional Science Association (ERSA), 2010)
Many welfare reforms undertaken in OECD-countries are directed towards enhancing efficiency in the administration and implementation of social security and social benefits. In this perspective the governance reforms in The Netherlands are an example of decentralisation through budgeting of means to municipalities. This brings about a unique twofold experiment in which we compare the efficiency changes in providing social assistance as a result of decentralisation and budgeting and the influence of policy measures at a local level. By using data envelopment analysis we assess the effect of the introduction of the new Work and Social Assistance Act (WSA) in 2004 on cost efficiency. By using a stochastic frontier analysis we assess the impact of municipal policy strategies on cost inefficiencies for the period 2005-2007. We find a clear positive effect of the WSA in 2004 on cost efficiency. Furthermore, we find that in the aftermath, when efficiency slowly dropped after 2005, there is a distinct impact of policy strategies municipalities adopt. Pursuing a strategy of activation raised efficiency significantly, whereas strict control or combinations of strategies led a (weak) fall in efficiency.
Keywords: 330